2003
DOI: 10.1074/jbc.m211899200
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-derived Growth Factor Induces the β-γ-Secretase-mediated Cleavage of Alzheimer's Amyloid Precursor Protein through a Src-Rac-dependent Pathway

Abstract: The ␤-amyloid peptide (A␤) present in the senile plaques of Alzheimer's disease derives from the cleavage of a membrane protein, named APP, driven by two enzymes, known as ␤-and ␥-secretases. The mechanisms regulating this cleavage are not understood. We have developed an experimental system to identify possible extracellular signals able to trigger the cleavage of an APPGal4 fusion protein, which is detected by measuring the expression of the CAT gene transcribed under the control of the Gal4 transcription fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
76
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(79 citation statements)
references
References 64 publications
2
76
1
Order By: Relevance
“…Thus, these different findings are most probably the result of the different GAL4-APP fusions used in these two studies. Indeed, the earlier work of Gianni et al (38) was an elegant study aimed at understanding the mechanisms regulating APP cleavage and not APP/Fe65-mediated transcription as in our work. Nevertheless, we tested whether c-Abl⌬XB also stimulated reporter gene activity that was driven by an APP-GAL4 DNA binding domain fusion in which GAL4 DNA binding domain sequences were fused to the C terminus of APP (APP-GAL4).…”
Section: C-abl Phosphorylates Fe65 To Enhance App/fe65 Transcriptionmentioning
confidence: 97%
See 3 more Smart Citations
“…Thus, these different findings are most probably the result of the different GAL4-APP fusions used in these two studies. Indeed, the earlier work of Gianni et al (38) was an elegant study aimed at understanding the mechanisms regulating APP cleavage and not APP/Fe65-mediated transcription as in our work. Nevertheless, we tested whether c-Abl⌬XB also stimulated reporter gene activity that was driven by an APP-GAL4 DNA binding domain fusion in which GAL4 DNA binding domain sequences were fused to the C terminus of APP (APP-GAL4).…”
Section: C-abl Phosphorylates Fe65 To Enhance App/fe65 Transcriptionmentioning
confidence: 97%
“…As such, phosphorylation of APP Tyr-682 or Fe65 Tyr-547 by active c-Abl appears not to influence APP/Fe65 interactions in any overt manner. Thus, while the stimulatory effect of c-Abl⌬XB on APP/Fe65 transcription is mediated by Fe65 Tyr-547 phosphorylation, this does not involve any marked changes in binding of APP to Fe65. Platelet-derived growth factor has recently been shown to induce ␤,␥-secretase cleavage of APP and this was characterized by monitoring the transcriptional activity of an APP-GAL4 fusion gene similar to the ones we used here (38). In the course of this study, active c-Abl was shown to have no effect on APP-GAL4-mediated transcription (38).…”
Section: C-abl Phosphorylates Fe65 To Enhance App/fe65 Transcriptionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, two different aspects of APP processing appear to be controlled by Rac1 and other small G proteins: ectodomain shedding (20), which is a prerequisite for ␤-␥-secretase cleavage, and the ␤-␥-secretase cleavage itself (21)(22)(23). In particular, overexpression of dominant negative (RacN17) or constitutively active (RacQL) mutants of Rac1 was demonstrated to inhibit or stimulate ␥-secretase-mediated APP processing (21), respectively, which suggests that Rac1 is crucial for the homeostasis of endogenous A␤ production.…”
Section: Alzheimer Disease (Ad)mentioning
confidence: 99%